Model Pengelolaan Pembelajaran Kelas Rangkap ( PKR ) Untuk Sekolah Dasar Yang Berada Di Wilayah 3T - Pebrianti, Tria; Septafi, Gesita; Wijaksono, Agus (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2024)
The concept of multigrade learning (PKR) is actually not only known in Indonesia but in various regions of the country, even in the US, there is PKR, especially in elementary schools. The PKR model is an ideal learning model according to teachers who have implemented the PKR system, namely by combining two classes in one lesson because it can describe an effective learning system, namely a learning experience in which students play a direct and active role in the learning environment as well as the relationship between interactions between teachers. and students are created directly. Another reason teachers implement PKR is to shorten time, namely by combining two courses with different levels at once. This is very effective for classes that have the same time, hours and subjects to receive the same material in one subject hour. the same and what is even more effective is that the two combined classes can only be managed by one teacher. This means there is a problem of a shortage of teaching staff in subject areas that are already filled.